2009
DOI: 10.3102/0013189x09338513
|View full text |Cite
|
Sign up to set email alerts
|

Design Tools in Didactical Research: Instrumenting the Epistemological and Cognitive Aspects of the Design of Teaching Sequences

Abstract: International audienceEuropean programmes of design research have developed distinctive types of apparatus to structure and support the process of didactical design. This article illustrates how intermediate frameworks and design tools serve to mediate the contribution of grand theories to the design process, by coordinating and contextualising theoretical insights on the epistemological and cognitive dimensions of a knowledge domain for the particular purposes of designing teaching sequences and studying thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
21

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 24 publications
1
63
0
21
Order By: Relevance
“…Alternatives to variation theory could be used to provide the design tools for learning study. For example, design based research in Europe attempts to derive such tools from 'grand' theories such as constructivism (Ruthven, Laborde, Leach and Tiberghien, 2009) …”
Section: Resultsmentioning
confidence: 99%
“…Alternatives to variation theory could be used to provide the design tools for learning study. For example, design based research in Europe attempts to derive such tools from 'grand' theories such as constructivism (Ruthven, Laborde, Leach and Tiberghien, 2009) …”
Section: Resultsmentioning
confidence: 99%
“…Reports on DBR studies often do not achieve satisfactory coherence among theoretical perspectives, instructional design, and a posteriori analysis (Abrahamson & Wilensky, 2007;Artigue, Cerulli, Haspekian, & Maracci, 2009;Kelly, 2004;Puntambekar & Sandoval, 2009;Ruthven, Laborde, Leach, & Tiberghien, 2009). We attempt to achieve such coherence as follows: (a) our post-hoc analytic attention to the multimodality of discourse in our empirical data resonates with the epistemological commitments underlying our embodied-design framework (Abrahamson, 2009d); and (b) probability is a suitable content domain for the study of multimodal reasoning, because the challenges of expressing randomness numerically may impel students to resort to alternative discursive genres such as metaphor (Rubin & Hammerman, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Research on the implementation of teaching and learning sequences (TLSs) has shown that they can be an effective way of feeding research into teaching practices [1][2][3][4][5]. The improvement derived from the use of TLSs has been shown in some cases to be significant even for teachers with little specific training of the specific TLS [6,7].…”
Section: Introductionmentioning
confidence: 99%